2009
DOI: 10.1002/jcp.21868
|View full text |Cite
|
Sign up to set email alerts
|

Calpain inhibitors prevent p38 MAPK activation and germ cell apoptosis after heat stress in pubertal rat testes

Abstract: Testicular injuries like torsion or cryptorchidism can cause massive germ cell death, which could have great impact on male reproductive health. In addition, it has been proposed that modern life style, in the form of underwear or sedentary work position, could increase the testicular temperature, induce germ cell apoptosis, reduce spermatozoa quality and promote male infertility. In this work we showed that a heat stress stimulus induced massive germ cells apoptosis, which was associated with p38 mitogen-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 66 publications
2
25
0
Order By: Relevance
“…Concurrently, heat stress inhibited LPS- or calpain-1/2 up-regulation-induced p38 activation in PMECs. Previous study has also demonstrated that calpain promotes p38 phosphorylation in heat stress-induced male germ cells [26]. We further show that activation of p38 mediated LPS-induced apoptosis as inhibition of p38 abrogated apoptosis induced by LPS.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Concurrently, heat stress inhibited LPS- or calpain-1/2 up-regulation-induced p38 activation in PMECs. Previous study has also demonstrated that calpain promotes p38 phosphorylation in heat stress-induced male germ cells [26]. We further show that activation of p38 mediated LPS-induced apoptosis as inhibition of p38 abrogated apoptosis induced by LPS.…”
Section: Discussionsupporting
confidence: 79%
“…Activation of all three subfamilies has been found to influence a multitude of cellular events such as cell growth and death, differentiation and inflammation in response to oxidative stress and LPS [2325]. It has been shown that the blockage of calpain suppresses p38 phosphorylation in heat stress-induced male germ cell apoptosis [26]. However, it remains to be elusive whether heat stress and calpain influence MAPK signalling in preventing/promoting PMECs apoptosis under septic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Different intracellular pathways are activated downstream of ROS production, among which the ASK1/p38MAPK pathway has been shown to be important in germ cell apoptosis after heat stress [153155]. p53, a master gene in apoptosis and a target of p38 MAPK (Figure 2), is activated in rats with experimental varicocele [156].…”
Section: Local Hypoxia: Varicocele and Testicular Torsionmentioning
confidence: 99%
“…Germ cell apoptosis has been shown to play an important role in controlling sperm output in many species and has been linked to infertility in humans (Feng et al, 1999;Weikert et al, 2004;Ji et al, 2009). Germ cells undergoing meiosis (spermatocytes) are highly sensitive to heat shock, ionizing radiation, growth factor deprivation, and chemotherapeutic agents (Russell, 2004;Bieber et al, 2006;Lizama et al, 2009;Silva et al, 2011). Many studies have shown the relevance of apoptosis in regulating spermatozoa output and eliminating damaged germ cells (Knudson et al, 1995;Beumer et al, 1998;Yin et al, 1998;Allemand et al, 1999;Feng et al, 1999;Honarpour et al, 2000;Yan et al, 2000a;Russell et al, 2002;.…”
Section: Apoptosis During Mammalian Spermatogenesismentioning
confidence: 99%